The M-form society : how American teamwork can recapture the competitive edge - Ouchi, William G. (Reading, Mass. : Addison-Wesley, 1984)
This book identifies three basic elements of M-Form society and shows how they must interact to be effective; namely a strong interlocking trade associations a responsive governmental organization the active participation of banks.
Includes bibliographical references and index.
ijb 19/10/2018
Loans
Keywords: Industrial policy